Entropy, Extropy and the Physical Driver of Irreversibility - Attila Grandpierre (Interdisciplinary Description of Complex Systems, 2012)
We point out that the fundamental irreversibility of Nature requires the introduction of a suitable measure for the distance from equilibrium. We show that entropy, which is widely held to be such a measure, suffers from the problem that it does not have a physical meaning, since it is introduced on the basis of mathematical arguments. As a consequence, the basic physics beyond irreversibility has remained obscure. We present here a simple but transparent physical approach for solving the problem of irreversibility. This approach shows that extropy, the fundamental thermodynamic variable introduced by Katalin Martinás, is the suitable measure for the distance from equilibrium, since it corresponds to the actual driver of irreversible processes. Since extropy explicitly contains in its definition all the general thermodynamic forces that drive irreversible processes, extropy is the suitable physical measure of irreversibility.